Gender analysis for one health: Theoretical perspectives and recommendations for practice - Friedson-Ridenour, Sophia; Dutcher, Tracy V.; Calderon, Claudia; DiPrete Brown, Lori; Olsen, Christopher W (EcoHealth, 2019)
One health emphasizes the interdependent health of humans, animals, and their shared environments and shows promise as an integrated, equitable transdisciplinary approach to important ecohealth issues. Notably, research or programming explicitly examining the intersection of gender and one health is limited, although females represent half of the human population and play important roles in human and animal health around the world. Recognizing these gaps, scholars from the University of Wisconsin-Madison in collaboration with United States Department of Agriculture convened a consultative workshop, ‘‘Women and One Health,’’ in 2016. This paper outlines the workshop methods and highlights outcomes toward shared terminology and integration of frameworks from one health, gender analysis, and women in agriculture. Further, recommendations for education, policy, and service delivery at the intersection of women’s empowerment and one health are offered as important efforts toward the dual goals of gender equality and sustainable health of humans,animals, and their shared ecosystems.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; amériques; environnement; femmes agricultrices; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; écosanté; états-unis